BREAST CANCER PROFILE IN VERY YOUNG WOMEN AT HAJI ADAM MALIK GENERAL HOSPITAL MEDAN - Ginting, Nichitri Agina; Betty (Talenta Publisher, 2020)
Abstract. Breast cancer is the most kind of cancer that happens to women, and it’s one of the cancer that can cause the major death in the world and in Indonesia. Breast cancer cases at age are very young tend to have lower percentages of old age, but have a bad prognosis. Family history of breast cancer because of the BRCA1 and BRCA2 mutation . Objective. The aim of this research is to study about breast cancer very young age profile in H. Adam Malik Medan General Hospital. From 2016-2018 based on age, family history and grading histology. Methods. In this descriptive research with cross-sectional study, the sample were collected from medical record of breast cancer patient in H. Adam Malik Medan General Hospital. This research use total sampling method and matched with inclusion and exclusion criteria. Results. Total of the sample is 160 subject. The majority of age group is 31-35 year’s old (81 subject or 51,0%). The majority of age menarche group is <12 year’s old (104 subject or 65,5%). Do not have family history (82 subject or 51,3%), and have a family history just found (78 subject or 48,8%). The majority of grading histology is grade 3 (68 subject or 42,5%). Conclusion. Sufferers of breast cancer at very young age is quite a lot with grade 3 on grading histology.Keyword: breast cancer, very young age, family history. Abstrak. Latar Belakang. Kanker payudara merupakan kanker yang paling sering terjadi pada wanita, dan merupakan salah satu kanker yang dapat menyebabkan kematian utama di dunia dan di Indonesia. Kasus kanker payudara pada usia sangat muda cenderung memiliki presentase yang lebih rendah diantara usia tua, namun memiliki prognosis yang lebih buruk. Riwayat keluarga pada kanker payudara dikarenakan adanya mutasi BRCA1 dan BRCA2. Tujuan. Mengetahui profil kanker payudara wanita pada usia sangat muda di Rumah Sakit Umum Pusat Haji Adam Malik Medan. Tahun 2016-2018 berdasarkan usia, riwayat keluarga dan grading histologi. Metode. Penelitian ini merupakan penelitian deskriptif dengan pendekatan cross-sectional. Penelitian ini dilakukan menggunakan data sekunder melalui data rekam medis penderita kanker payudara di Rumah Sakit Umum Pusat Haji Adam Malik Medan. Besar sampel ditentukan dengan metode total sampling dan disesuaikan dengan kriteria inklusi dan eksklusi. Hasil. Diperoleh total 160 sampel. Kelompok usia terbanyak adalah usia 31-35 tahun sebanyak 81 penderita (51,0%). Usia menarche terbanyak pada kelompok usia <12 tahun sebanyak 104 penderita (65,5%). Tidak memiliki riwayat keluarga sebanyak 82 penderita (51,3%), dan memiliki riiwayat keluarga ditemukan sebanyak 78 penderita (48,8%). Grading histologi terbanyak adalah grade 3 sebanyak 68 penderita (42,5%). Kesimpulan. Penderita kanker payudara pada usia sangat muda cukup banyak dengan grade 3 pada grading histologi.Kata Kunci: kanker payudara, usia sangat muda, riwayat keluarga